RELEVANSI VASTUSHASTRA DENGAN KONSEP PERANCANGAN JOGLO YOGYAKARTA - Dwi Retno Ambarwati (Jurnal Penelitian Humaniora, 2009)
This study is aimed to analyse the relevance between Vastushastra and the concept design of Joglo Yogyakarta by making a comparation between both of them and the further analysis is the identification of the matter that cause the relevant and irrelevant between them. The result of this study indicate that basically there are some relevances between Vastushastra and the concept design of Joglo Yogyakarta on the cosmology concept, the effort to achieve the primary goal of life by creating and keeping the harmony with the nature, an effort in balancing the energy of nature, believing the influence of nature in human life, and the relevance in choosing the shape of the house (square shape). In the other side, the irrelevants are in choosing the orientation of the house and the room configuration. Those irrelevants caused by the creativity of Javanesse people, and the condition of nature dan geographic.